Descrição de sítio críptico inédito e identificação de novos ligantes para a proteína PD-L1 por dinâmica molecular com cossolventes - Costa, Andrielly Henriques dos Santos (2022)
Blockage of the PD-1–PD-L1 checkpoint pathway has emerged as a promising treatment for tumors with high gene instability. Understanding the mode of interaction between the proteins involved in this pathway has supported the development of effective inhibitors of the class of antibodies, peptides, and small molecules. However, the use of small ligands for PD-L1 modulation has limitations given the low susceptibility of the interface region to interact with this class of molecules, hence opening space for the search for new cavities. In this context, the investigation of cryptic sites (transient occluded sites) emerges as an alternative for the modulation of the PD-L1 protein. Research in this emerging field has allowed the rational development of the drugs for proteins of significant pharmacological interest and low potential for interaction with small ligands. Accordingly, in silico tools emerge as a powerful approach in searching for new cavities and understanding systems’ structural dynamics. Thus, the present work aimed to identify a new cryptic site in PD-L1 through molecular dynamics simulations with cosolvent (MixMD) and investigate a small molecule for the target cavity. We showed that nonpolar aromatic probes were more effective in interacting with the surface of PD-L1. Prominently, benzene was responsible for exposing a cryptic site close to the C''D loop. This cavity proved to be highly flexible, having two transient openings. The predictive analysis of the drugscore (0.84) suggests that small molecules can act modulating such a cavity. Furthermore, virtual screening identified the indacaterol, which has been shown to induce an effect like conformational selection at the PD-L1 interface. The energetic description of the protein complexes suggests that indacaterol disfavors the interaction of PD-L1 with PD-1, showing promising results for the selection of new drugs. Thereby, this work suggests new PD-L1 interaction regions that can be targeted for the rational design of molecules for the treatment of oncological diseases, as well as a possible ligand to be used as a starting point.